(untitled) (CIPEEX, 2025)
The project involves developing a stock management system that provides a detailed view of warehouse shelves, showing the exact location of products along with critical information such as batch number, expiration date, and quantity of each item. The system uses a graphical interface to visually represent the shelves and the products stored on them. Each product is associated with a specific shelf, and the volume of each shelf is monitored in real time by Arduinos. These devices are responsible for controlling and recording the available shelf space, ensuring accurate and efficient stock management.In addition to the visual representation of shelves, the system keeps detailed records of the batch number, expiration date, and quantity of each product. Real-time monitoring of the shelves’ volume is conducted through the use of Arduinos, which helps maintain accurate inventory control. The system also allows users to view and update product and shelf information instantly, further optimizing stock management.The overall objective is to create an integrated system that enhances the organization and management of inventory, improving the efficiency of product control and administration. The inclusion of Arduinos for volume monitoring adds a technological aspect that ensures accuracy and real-time updates, making the stock management process more reliable and streamlined.